Photoelectric multilevel memory device based on covalent organic polymer film with keto–enol tautomerism for harsh environments applications - Zhou, Pan-Ke (2023)
Covalent organic polymers (COPs) memristors with multilevel memory behavior in harsh environments and photoelectric regulation are crucial for high-density storage and high-efficiency neuromorphic computing. Here, a donor–acceptor (D–A)-type COP film (Py-COP-3), which is initiated by keto–enol tautomerism, is proposed for high-performance memristors. Satisfactorily, the indium tin oxide (ITO)/Py-COP-3/Ag device demonstrates multilevel memory performance, even in high temperatures, acid-base corrosion, and various organic solvents. Moreover, the performance can be modulated by the photoelectric effect to maintain a great switching behavior. By contrast, Py-COP-0, with similar structure and chemical composition to Py-COP-3 but without keto–enol tautomerism, exhibits binary storage performance. Further studies unravel that both the formation of conductive filaments and charge transfer within D-A Py-COP-3 film contribute to the resistive switching behavior of memory devices.